THE SEARCH OF EQUIVALENCE IN TRANSLATING SEVEN CHARACTER TRAITS OF DHYANA PURA UNIVERSITY - Putu Chris Susanto; Putu Chrisma Dewi; Made Nyandra (International Conference on Languages and Arts, 2014)
Character building is of high importance at the Bali Dhyana Pura University (Undhira). The University Statute (2012) prescribes seven organizational values, which is a set of virtues, norms, beliefs, and actionable principles within an organization. This article explores the translation equivalence of these seven values, from the source language Bahasa Indonesia intothe target language of English. Some incorrectness and inconsistencies were found, as well as less than optimal translation equivalence that necessitates revision.Employing a model of analysis derived from the theories of equivalence from Vinay and Darbelnet (1958), Nida (1964), Catford (1965), Baker (1992), Bayar (2007), and Pym (2010), authors analyze the translation process and outcome of these organizational values. This study of recommends that the term ‘character traits’ be used to signify the organizational values of Undhira, consisting of seven character traits: (1) Self-Confidence, (2) Integrity, (3) Diversity, (4) Servant Leadership, (5) Professionalism, (6) Entrepreneurship, and (7) Global Outlook.   Keywords: character education, character traits,equivalence, organizational values, translation